(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The main task of this investigation is evaluation of patented (LV 14604 B) biomass briquetting mechanism. Theoretical relationship between necessary drive force and resistance force during pressing in die was determined. Briquettes from grinded common reed (Phragmites Australis) or common reed-peat mixture were produced with designed experimental briquetting press. Density of common reed briquettes depending on the size of particles was stated. Density of briquettes obtained during compacting was from 826.3±16.4 to 934.5±35.1 kg m-3. The minimum of density 826.3±16.4 kg m-3 had briquettes with particles from 6 mm grinding screen, but maximum density 934.5±35.1 kg m-3 had briquettes, when particles from 1.5 mm grinding screen had been used. Compositions of reed particles with peat allow obtaining briquettes density > 1000 kg m-3 if peat proportion in mixture is 30%. Results of theoretical and experimental investigation show that the designed pressing mechanism can be recommended for mobile biomass briquetter design.